Kencur Supplementation for Attenuating Exercise-Induced Muscle Damage and Delayed-Onset Muscle Soreness - Irawan, Roy Januardi; Sulistyarto, Soni; Rimawati, Nanda (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Delayed Onset Muscle Soreness (DOMS) is a pain that occurs after uncustomized eccentric exercise and can happen to anyone, both those who are athletes and other individuals. DOMS is usually felt 24-72 hours after exercise or activities that use eccentric movements, which interfere with the athlete’s training activities and other individuals’ daily activities. This study aimed to determine the effectiveness of kencur extract supplementation (kaempferia galanga linn) on DOMS and creatine kinase (CK) plasma levels after eccentric exercise. This research is quasi-experimental, using a randomized control group design as the design in this study. Research subjects (n = 28) were randomly divided into 2 groups, namely the kencur extract group (200 mg/day) and the placebo group (corn flour). The supplementation process in both groups was carried out for 5 days (3 days before and 2 days after) the eccentric exercise. DOMS pain (VAS) and blood samples (CK plasma) were taken 24 hours (pre) and 48 hours (post) after eccentric exercise. The destructive drill uses the 5 x 20 Eccentric depth jump drill. The data obtained in the form of changes in DOMS pain and CK plasma were then analyzed using ANOVA with sig. 0.005. Supplementation of galingale extract was effective in reducing DOMS pain with p = 0.008 (0.05) and CK plasma value p = 0.000 (0.05) compared to placebo after eccentric exercise. Supplementation of galingale extract (Kaempferia Galanga Linn) for 5 days is effective as an effort to reduce the risk of DOMS pain sensation and reduce the increase in muscle damage with CK as a marker after eccentric exercise.